Rostros - Centro de Estudios Teológicos de la Amazonía (CETA) (My University, 1900)
SPANISH: La fotografía muestra a Iván Vásquez Valera, es un político peruano, fue Presidente Regional de Loreto entre 2007 y 2014 y alcalde provincial de Maynas entre 1999 y 2002
ENGLISH: The photograph shows Iván Vásquez Valera, is a Peruvian politician, he was Regional President of Loreto between 2007 and 2014 and provincial mayor of Maynas between 1999 and 2002.

SPANISH: La fotografía muestra a Iván Vásquez Valera, es un político peruano, fue Presidente Regional de Loreto entre 2007 y 2014 y alcalde provincial de Maynas entre 1999 y 2002
ENGLISH: The photograph shows Iván Vásquez Valera, is a Peruvian politician, he was Regional President of Loreto between 2007 and 2014 and provincial mayor of Maynas between 1999 and 2002.
Faces
Keywords: Iquitos (Perú)|~|Actividades culturales|~|Perú|~|Perú--Cultura Amazónica|~|Perú--Personajes Religiosos